Apoptosis and Antioxidant Activities of Catharanthus rosues [L] G.Don Extract on Breast Cancer Cell Line - Widowati, Wahyu; Mozef, Tjandrawati; Risdian, Chandra; Ratnawati, Hana; Tjahyani, Susy; Sandra, Ferry (Indonesian Journal of Cancer Chemoprevention, 2010)
Tapak dara or Madagascar Periwinkle (Catharanthus roseus [L] G.Don), a natural plant, is empirically reported to have promising anticancer activity. To elucidate its mechanism, a research was conducted to investigate the possible ethanol extract ofÃÂ  C.ÃÂ  roseus in inducing apoptosis on breast cancer cell line (T47D). Antioxidant activity of C. roseus was investigated as well. Sub-G1 flowcytometric apoptotic analysis result showed that extract of C. roseus at 6.25 ÃÂ¼g/mL induced apoptosis for 26.365%. Increasing extract concentration resulted an increasing apoptotic level as well, extract at concentration of 12.5 ÃÂ¼g/mL induced apoptosis for 22.235%. ÃÂ Meanwhile doxorubicin at concentration of 10ÃÂ  ÃÂ¼g/mL induced apoptosis for 36.055%. The antioxidant activity was determined by usingÃÂ  in vitro assay: inhibition ofÃÂ  2,2-diphenyl-1-picrylhydrazyl (DPPH) scavengingÃÂ  activity. Antioxidant activity ofÃÂ  C. roseus extract were compared to quercetin and butylated hydroxyanisol (BHA), as positive controls.ÃÂ  The results showed that DPPH IC50 of C. roseus extract, quercetin and BHA were 358.411 ÃÂ¼g/mL, 19.200 ÃÂ¼g/mLÃÂ  andÃÂ  94.178ÃÂ  ÃÂ¼g/mL, respectively. We suggest thatÃÂ  C. roseus extract had a potential anticancer activity by inducing apoptosis.